Improving energy efficiency of buildings with mansard roofs - Zhvan, V.; Donenko, І.; Marchenko, M. (Ways to Improve Construction Efficiency, 2019)
In the article, the author provides data on the state of energy saving both in the houses of the old buildings and the modern ones built in the last 10 years, as well as in those that are just being built. The author made an analysis of the main structural and technological solutions of buildings and their impact on the energy efficiency of buildings. Based on this analysis, the author found that for houses with sloping roofs and attic rooms under them, it is important to improve the energy efficiency of such houses, to solve problems, to reduce energy costs for cooling attic rooms in summer and to preserve heat in winter. The author proposed a solution to the regulation of this problem, and discussed in this article. A patent of Ukraine has been received for this decision.